Faktor Faktor yang Mempengaruhi Perilaku Pencegahan TB Paru: Studi Kasus pada Keluarga yang Tinggal Serumah dengan Penderita di Kecamatan Terisi - Widyastuti, Setyo Dwi; Fauzi, Muhammad; Febrian, Luthfan (Preventif : Jurnal Kesehatan Masyarakat, 2024)
Tuberculosis is a globally concerning disease. To break the chain of transmission, preventive efforts against Pulmonary Tuberculosis (TB) are necessary for family members living with TB patients. The aim of this study is to determine the factors influencing TB prevention behavior among families living with TB patients in Terisi District. The research employs quantitative analytical methods with a Cross-Sectional approach. The study population consists of all family members living with TB patients in Terisi District, totaling 86 respondents. Data analysis involves univariate, bivariate, and multivariate analyses. Bivariate analysis utilizes the Chi-Square test, while multivariate analysis employs Multiple Logistic Regression. Independent variables studied include the impact of perceived susceptibility, severity, benefits, barriers, and cues to action on the dependent variable, the TB prevention behavior of family members. Bivariate analysis results indicate significance for perceived susceptibility (P value=0.002), severity (P value=0.000), benefits (P value=0.014), barriers (P value=0.105), and cues to action (P value=0.008). Multivariate analysis reveals that perceived severity holds the greatest influence on TB prevention behavior (OR=25.144). Recommendations from this study include providing education on TB prevention and establishing TB advocates who guide and motivate family members in TB prevention. Thus, it is hoped that family members residing with TB patients will consistently adopt TB prevention behavior.